Determination of trace elements in human milk, cow's milk, and baby foods by flame AAS using wet ashing and microwave oven sample digestion procedures - Yaman, M; Çokol, N (Atomic Spectroscopy Press Ltd, 2004)
Three sample digestion procedures using dry and wet ashing and microwave oven are compared for the flame atomic absorption spectrometry analysis of human milk, cow's milk, and baby food samples. Copper, Mn, Zn, and Fe were determined in the digestion solutions. Various acid mixtures were examined in conventional wet digestion using a hot plate. It was found that the mixture of HNO3/H2O2 (1:1) was simple to use and provided best results in comparison to either HNO3/HClO4 or HNO3 in wet ashing procedure. The analytical parameters show that the microwave oven digestion procedure provided best results as compared to the wet ashing procedure. Microwave sample digestion is an accurate, simple, and fast method for the flame AAS determination of Cu, Mn, Zn, and Fe in human milk, cow's milk, and baby formulas, except for the determination of Fe in rice flour and baby biscuits.
Keywords: Copper; Iron; Speciation; Soils